Anodic Stripping Voltammetric Determination of Trace Cadmium Using Carbon Paste Electrode Modified by 1-Butyl-3-methylimidazolium Tetraflouroborate Ionic Liquid - Hung, L.Q.; Anh, N.H.; Ha, V.T.T.; Phong, P.H. (Asian Journal of Chemistry, 2014)
Carbon paste electrodes modified with ionic liquid and carbon nanotubes were used for the determination of trace cadmium by anodic stripping voltammetry. The electroanalytical performance for the determination of Cd2+ on the ionic liquid-carbon paste electrode and ionic liquid-carbon nanotube carbon paste electrode (IL-CPE and IL-CNT-CPE) were better than that on the pure carbon paste electrode. Compared with two others, the best electrode obtained in this study was IL-CNT-CPE. The measuring conditions were also optimized. The measurement of trace cadmium on the IL-CNT-CPE had the best response under the conditions of 0.10 M phosphate buffer solution (PBS) (pH 4), deposition potential of -1 V and a deposition time of 240 s. The IL-CPE and IL-CNT-CPE revealed highly linear behaviour in the concentration range of 20-100 ppb and 5-220 ppb with detection limits of 5 ppb and 1.48 ppb respectively. The developed sensor has been applied to the determination of Cd2+ in real water samples with satisfactory results.